Learning of the quechua language and the syllabus of the subject in the Professional School of Administration of the Andina University Of Cusco- Sicuani Branch 2022 - Zanabria Diaz , Maruja (2024)
The purpose of this study is to investigate the relationship between the learning of the Quechua language and the syllabus of the Quechua workshop or native language in the students of the first cycles of the Professional School of Administration of the Andean University of Cusco, Sicuani branch. In this sense, a quantitative type of research was proposed, making use of the correlational design; specific theoretical concepts on learning and syllabus were required, to then apply as instruments for collecting information and measurement; a written test that allowed measuring the learning level of students of the first cycles in the professional school of Administration and an observation guide instrument that allowed the student to systematically observe the structure of the syllabus of the subject with the development of topics and themes included in the syllabus, for this purpose a group of 32 students was considered.             Although statistically there is a correlation between both variables that reaches 0.350 with a p-value of 0.049, we conclude that this relationship is not significant because the syllabus factors that influence are more informative than substantial in the training of students. Therefore, we recommend replicating this research in other professional careers and reviewing the contents of the syllabus to improve it and make it meaningful in professional training.